PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KEPUASAN KERJA KARYAWAN PADA RS MARTHA FRISKA (BIDANG KEPERAWATAN) - Sartito Sianturi; Roma Diana Maria Sihombing; Lenta Marianti Sitinjak; Rizki Yuspantrisia (JURNAL ILMIAH SOCIO SECRETUM, 2020)
Competence is a fundamental characteristic possessed by someone who has a direct influence on, or can predict good work performance. Competence is needed in improving the quality of human resources in advancing the company. Besides, training competencies can affect the company’s progress. That is why companies need to provide training to their employees. The purpose of this study was to determine the effect of competence and training on employees’ job satisfaction at Martha Friska Hospital. The analysis method used multiple linear regression analysis. The study population was 212 employees with a sample of 138 respondents. The results of the study indicated that both competency and training influenced employees’ job satisfaction